Shahjalal Fertilizer Company Limited (SFCL): in Retrospect - Quader, AKMA (Chemical Engineering Research Bulletin, 2021)
This is a reflection on the implementation of Shahjalal Fertilizer Project (SFP) what is today Shahjalal Fertilizer Co. Ltd. (SFCL). This deals with a wide range of issues covering technical, contractual, and administrative involving SFP, General Contractor, sub-contractors, Process Licensors and vendors. These arose because of mindset, interpretation of contract clauses, inexperience, expectation and frustration of both Owner and General Contractor. Lessons learned would enable BCIC to undertake such projects in future by avoiding pitfalls and missteps of SFP. Chemical Engineering Research Bulletin 21(2020) 1-13